Quantitative assessment of the effects of trypsin digestion methods on affinity purification-mass spectrometry-based protein-protein interaction analysis - Zhang, Yueqing (J Proteome Res, 2017)
Affinity purification-mass spectrometry (AP-MS) has become the method of choice for discovering protein-protein interactions (PPIs) under native conditions. The success of AP-MS depends on the efficiency of trypsin digestion and the recovery of the tryptic peptides for MS analysis. Several different protocols have been used for trypsin digestion of protein complexes in AP-MS studies, but no systematic studies have been conducted on the impact of trypsin digestion conditions on the identification of PPIs. Here, we used NFκB/RelA and Bromodomain-containing protein 4 (BRD4) as baits and test five distinct trypsin digestion methods (two using “on-bead,” three using “elution-digestion” protocols). Although the performance of the trypsin digestion protocols change slightly depending on the different baits, antibodies and cell lines used, we found that elution-digestion methods consistently outperformed on-beads digestion methods. The high-abundance interactors can be identified universally by all five methods, but the identification of low-abundance RelA interactors is significantly affected by the choice of trypsin digestion method. We also found that different digestion protocols influence the selected reaction monitoring (SRM)-MS quantification of PPIs, suggesting that optimization of trypsin digestion conditions may be required for robust targeted analysis of PPIs.